On the Road – My life as a Theater Creator (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
The text presents a trajectory of the actress, director and Israeli singer Yael Rasooly.Keywords: Theater of animation. Yael Rasooly. Creation process.